Local environmental governance and policy implementation: Variegated environmental education in three districts in Tianjin, China - Outi Luova (Sage Publications Ltd., 2022)
Variation in the implementation of environmental policies in urban China has received widespread scholarly attention, but the extensive heterogeneity in local governance frameworks has remained understudied. Leaning on the new institutional theory, this article suggests that the concept of institutional configuration can bring structure to the analysis of local complex governance frameworks and help identify factors that create different approaches to environmental policies. This study analyses the construction of approaches to new environmental education policies in three urban districts in Tianjin to illustrate how the suggested conceptual framework applies to centrally-administered Chinese cities. The findings show that different combinations of formal and sociocultural factors emerge as decisive in the institutional configuration of each district. This study also reveals new interesting nuances in the motivations behind environmental policy implementation.